x^

**2**-225 = (x+15)(x-15) 9x^**2**-196y^**2**= (3x + 14)(3x - 14) 2x^**2**-50 =**2**(x^**2**- 25) =**2**(x+5)(x-5) 4x^**2**-(y+z)^**2**= (2x + (y+z))(2x - (y+z)) = (2x + y + z)(2x - y - z) (x+y)^**2**-z^**2**= ((x+y) + z)((x+y) - z) = (x + y + z)(x + y - z) 9y^**2**-(x-**2**)^**2**...4 Answers · Science & Mathematics · 1

**2**/01/**2**007... the product rule. Hence: U can write the question as 2x (1-x^

**2**)^-**2**=2x (-**2**) (-2x) (1-x^**2**)^-1 + (1-x^**2**)^-**2**(**2**) 1st derivative = 8x^**2**(1-x...4 Answers · Science & Mathematics · 08/04/

**2**007**2**^(**2**x +**2**) = 64 First off, 64 is a power of**2**. In fact, 64 =**2**^6, so**2**^(2x +**2**) =**2**^6 Same base on both sides of the equation, so we may equate the exponents at this point. 2x +**2**= 6 2x = 4 x =**2**4 Answers · Science & Mathematics ·

**2**9/06/**2**007Let √

**2**(√**2**(√**2**(√**2**(√**2**...)))) = x => √(**2**x) = x =>**2**x = x^**2**=> x^**2**-**2**x = 0 => x (x -**2**) = 0 => x =**2**... [because x is not zero] Another method: √**2**...1 Answers · Science & Mathematics · 15/04/

**2**01**2****2**x √(3) /**2**= [**2**√(3)] /**2**= √3 Unless you meant:**2**√(3/**2**) = [**2**√(3) / √(**2**)] x [√(**2**) / √(**2**)] = [**2**√(6)] /**2**= √6 Remember, you can't have radicals in...9 Answers · Science & Mathematics · 05/05/

**2**010tan(theta/

**2**)=sin(theta/**2**)/(cos(theta/**2**) first find sin(theta/**2**) sin^**2**(theta/**2**)=1/**2**(1-cos(theta)) cos(theta)=-3/5 sin^**2**...3pi/4 is in the 2nd quadrant then sin(theta/**2**) is positive and cos(theta/**2**) is negative...1 Answers · Science & Mathematics ·

**2**6/10/**2**011The x ≤

**2**restriction is important because -(x -**2**)^**2**is not one-to-one and thus doesn...find the inverse mostly like we do with out functions. We let y = -(x -**2**)^**2**and then interchange x and y and then re-solve for y. Interchanging x...1 Answers · Science & Mathematics · 30/08/

**2**010a = √

**2**+ √3 a² = 5 +**2**√**2**√3 a³ =**2**√**2**+ 6√3 + 9√**2**+ 3√3 = 9(√**2**+ √3) +**2**√**2**= 9a +**2**√**2**√**2**= (1/**2**)a³ - (9/**2**)a.1 Answers · Science & Mathematics · 30/03/

**2**016integral x^

**2**/(**2**-x)^**2**dx do long division: = integral (4/(x-**2**)+4/(x-**2**)^**2**+1) dx Integrate the sum term by term and factor...integral of 1/s is log(s): = 4 log(s)+4 integral 1/u^**2**du+ integral 1 dx The integral of 1/u^**2**is...3 Answers · Science & Mathematics · 17/04/

**2**010∫ x^

**2*** √(x -**2**) dx ===> by parts u = x^**2**du =**2**x dx dv = (x -**2**)^(1/**2**) dx s = x -**2**ds = dx...3) * (x -**2**)^(3/**2**) - ∫ (**2**/3) * (x -**2**)^(3/**2**) ***2**x * dx x^**2*** (**2**/3) * (x -**2**)^(3/**2**) - ∫ (4/3) * (x -**2**)^(3/**2**) * x * dx ===> by...5 Answers · Science & Mathematics · 04/06/

**2**011